Relationship Between HbA1c Level with Retinal Nerve Fiber Layer Thickness in Diabetic Retinopathy - Febrina Art; AK Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2019)
Abstract Background: Diabetes mellitus (DM) have a direct effect to retinal neural tissue. Diabetic retinopathy slowly proggress with reserved visual acuity and no symptoms in early stage. Retinal nerve fiber layer thickness significantly decrease in type 2 diabetes mellitus patients related to glycemic blood level. Purpose: To analyze the relationship between HbA1c level and retinal nerve fiber layer thickness in diabetic retinopathy patients. Methods: A cross sectional analytical study was conducted in RSUP dr. Mohammad Hoesin Palembang from October 2017 until March 2018. Sixty eight type 2 diabetes mellitus patients consist of various grade of diabetic retinopathy. Measurement of HbA1c level was performed on these samples and retinal nerve fiber layer thickness was measured by Optical Coherence Tomography (OCT). Results: There is a significant relationship between duration of DM with RNFL thickness (p = 0,002). There is a significant relationship between hypertension with RNFL thickness (p = 0,007). There is a significant relationship between HbA1c level with RNFL thickness in all quadrants (superior, nasal, inferior quadrants p = 0,000, temporal quadrant p = 0,011). The most important factor of RNFL thinning in superior, nasal and inferior quadrants is HbA1c level (superior and nasal adjusted p value 0,002, inferior adjusted p value 0,002) while in temporal quadrant is hypertension (adjusted p value 0,042). Conclusion: There is a significant relationship between HbA1c level with RNFL thickness in all quadrants in which the patients with HbA1c > 7% have a higher risk of thinner RNFL compared to patients with HbA1c ≤ 7%.